Macrophage-Laden Gold Nanoflowers Embedded with Ultrasmall Iron Oxide Nanoparticles for Enhanced Dual-Mode CT/MR Imaging of Tumors - Yucheng Peng; Xiaomeng Wang; Yue Wang; Yue Gao; Rui Guo; Xiangyang Shi; Xueyan Cao (MDPI AG, 2021)
The design of multimodal imaging nanoplatforms with improved tumor accumulation represents a major trend in the current development of precision nanomedicine. To this end, we report herein the preparation of macrophage (MA)-laden gold nanoflowers (NFs) embedded with ultrasmall iron oxide nanoparticles (USIO NPs) for enhanced dual-mode computed tomography (CT) and magnetic resonance (MR) imaging of tumors. In this work, generation 5 poly(amidoamine) (G5 PAMAM) dendrimer-stabilized gold (Au) NPs were conjugated with sodium citrate-stabilized USIO NPs to form hybrid seed particles for the subsequent growth of Au nanoflowers (NFs). Afterwards, the remaining terminal amines of dendrimers were acetylated to form the dendrimer-stabilized Fe3O4/Au NFs (for short, Fe3O4/Au DSNFs). The acquired Fe3O4/Au DSNFs possess an average size around 90 nm, display a high r1 relaxivity (1.22 mM−1 s−1), and exhibit good colloidal stability and cytocompatibility. The created hybrid DSNFs can be loaded within MAs without producing any toxicity to the cells. Through the mediation of MAs with a tumor homing and immune evasion property, the Fe3O4/Au DSNFs can be delivered to tumors more efficiently than those without MAs after intravenous injection, thus significantly improving the MR/CT imaging performance of tumors. The developed MA-mediated delivery system may hold great promise for enhanced tumor delivery of other contrast agents or nanomedicines for precision cancer nanomedicine applications.